المعجم في المصلطحات التعليمية وتطويره في تعليم اللغة العربية (بالتطبيق على طلبة قسم تعليم اللغة العربية بجامعة السلطان أماي الإسلامية الحكومية غورونتالو) - Ratni Bt. Hj. Bahri; Mukhtar I Miolo (Universitas Muhammadiyah Gorontalo, 2020)
Indeed, the urgency of the dictionary in foreign language learning - especially Arabic - is something that does not need a special report when we realize that past studies have confirmed that a teacher reduces his role in a lesson. A teacher should focus more on learning to students by using media that can help students to acquire language in a successful and effective way. A dictionary would be very effective if designed according to the needs of the students.The purpose of this study is to: 1) describe the characteristics of the dictionary in terms of learning that has been developed 2) describe the extent to which the feasibility of the developed dictionary 3) Describe the effectiveness of learning Arabic language using a developed dictionary.The research method used in this research is research and development method of Sugiyono development model. The assessment steps are: 1) Needs analysis, 2) Data collection, 3) Product design, 4) Product development, 5) Expert validation, 6) Product revision, 7) Field test, 8) Product revision, and 9) Product end. Research data in the form of quantitative and qualitative data. The data source of this research is one expert Arabic field and one design expert. The data collection techniques used are questionnaires and tests.The results show that: 1) the characteristics of this dictionary lies in the specificity of this dictionary for learning Arabic. The number of vocabularies in this dictionary is about 2000 vocabularies. Everything is arranged alphabetically to make it easier for readers. 2) The percentage value indicates that the dictionary is eligible for use by IAIN students Sultan Amai Gorontalo 3) The use of this dictionary is effective to assist students in translating terms related to learning.